PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN CV. DARCO JAKARTA - M. Andhika Rahman; Freddrick Tiagita P (Jurnal Ekonomi dan Industri, 2022)
Purpose to analyze the effect of compensation and work environment on employee performance of CV. Darco Jakarta. This research is included in the category of causal associative research using a quantitative approach. The population in this study were employees of CV. Darco Jakarta, totaling 30 people. The sampling method in this study is the saturated sample technique where all members of the population are sampled. The research method using simultaneous and partially linear regression analysis. The results of the study indicate that simultaneous or partially, compensation and work environment have a positive and significant effect on employee performance of CV. Darco Jakarta.